Antidiarrheal Activity of The Combination of Ethanol Extracts of Turmeric Rhizomes, Gall oak Leaves, Guava Leaves and Meniran Herbs - Sumi Wijaya; Lisa Soegianto (Jurnal Jamu Indonesia, 2017)
Diarrheal disease is an endemic disease in Indonesia and also a potential disease that can cause death. In practice, the use of traditional medicines derived from plants still being considered by society due to its viability, economic factors and safety reasons. Several plants worked as antidiarrheal agents with the mechanism actions of (1) antibacterial (inhibited the growth of Escherichia coli, Shigella dysenteriae, Shigella flexneri, Staphylococcus aureus and Salmonella Typhi); (2) reduced the contraction of intestinal as results in the reduction of pain and the reduction of frequency of defecation or; (3) both mechanism of actions. Thus the purpose of the present study is to evaluate antidiarrheal activity of the combination of plant extracts which have been proved to have antidiarrheal activity. Turmeric (Curcuma domestica) rhizomes, gall oak (Quercus lusitanica) leaves, guava (Psidium guajava) leaves and meniran (Phyllanthus niruri) herbs were used for this combination. The purpose of this combination was to minimize the doses (based on literature reviews turmeric at 5% and Meniran 10% inhibited the growth of Escherichia coli and Staphylococcus aureus, meanwhile guava leaves at 150 mg/kg BW and gall oak leaves at 10% reduced diarrhea in animal tested). Maceration was chosen for the extraction method using ethanol 96% as the solvent. Protection and transit intestinal method with loperamide HCl as comparison drug and castor oil for the induction of diarrhea were used for antidiarrheal activity, meanwhile diffusion and dilution methods using, inhibition zones, minimum inhibition concentration and minimum bactericidal concentration parameters were used for antibacterial activity. Tetracycline HCl with the concentration of 30 µg was used for the control. The results revealed that the combination of plant extract with the doses of 200 mg/KgBW (1:1:1:1) reduced diarrhea in mice with relaxation of smooth muscle and showed weak antibacterial effects on Eschericia coli and Staphylococcus aureus but strongly inhibited the growth of Salmonella Typhi.